On Quinary [6, 4] Error Correcting Codes. (3rd March 2016) - Dey, Partha Pratim; Kumar Ghose, Apu
Abstract: In this paper we investigate the existence, equivalence and weight distribution and some other features of [6, 4] error correcting codes over GF (5).